User Acceptance Research on The Legal Documentation and Information Network Platform in Majalengka Government - Hudoarma, Fathurahman Ma'ruf; Sensuse, Dana Indra; Lusa, Sofian; Putro, Prasetyo Adi Wibowo (The Indonesian Journal of Computer Science, 2023)
The evaluation of JDIH platform's user acceptance in accessing legal documentation and information has not been conducted, resulting in an average visitation rate of only 15%. The objective of this study is to identify the factors that influence user acceptance of the JDIH platform and provide recommendations for enhancing visitor traffic to the JDIH platform. This study was conducted using a mixed methods approach, incorporating the Technology Acceptance Model as its foundational theory and integrating the Innovation Diffusion Theory, DeLone & McLean IS Success Model, and Habit variables as its external constructs. The quantitative data processing method was conducted using the PLS-SEM method with the assistance of the SmartPLS application. The findings of this study reveal that the factors of relative advantage, habit, perceived benefits of use, and intention to use significantly influence user acceptance in utilizing the JDIH platform.